A Valuable Contribution to the History of Sociology in Yugoslavia - Mitrović, Ljubiša (Sociološki pregled, 2023)
The paper is a review of the scientific contribution of Russian sociologist, Professor Zinaida T. Golenkova, PhD, particularly in the field of research of Yugoslav (and Serbian) sociology in the period of its socialist development, as well as Golenkova’s personal engagement in the cooperation between (Soviet) Russian and (Yugoslav) Serbian sociologists in the period from the 1960s to date. Having in mind the wealth of history of Serbian and Yugoslav sociology, to the research of which Golenkova largely contributed, the paper pleads for the development of a special academic, sociological discipline that would deal with the development of sociology in Serbia.